Research progress of ferroptosis pathway and its related molecular ubiquitination modification in liver cancer - Yao, Silin; Quan, Yi (Frontiers in Oncology, 2025)
As a new type of programmed cell death, ferroptosis is characterized by iron metabolism disorder and reactive oxygen species (ROS) accumulation, and is involved in regulating the occurrence and development of cancer cells. Especially in the field of liver cancer treatment, ferroptosis shows great potential because it can induce tumor cell death. Ubiquitination is a process of protein post-translational modification, which can affect the stability of proteins and regulate the progress of ferroptosis. This article reviews the research progress of ubiquitination modification of molecules related to ferroptosis pathway in the regulation of liver cancer, providing a new strategy for the treatment of liver cancer.